Experimental Study Of The Performance Of The Thermal Energy Water Pump Using Tilled Evaporator - Halim, Christian (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2022)
Water is one of the important or basic needs for human life. The availability of water in Indonesia is an advantage that our nation has that has not been optimized. Generally, water pumps are driven by electrical energy, but it is possible to be driven by other energy, namely petroleum energy (with a combustion motor). Alternative energy that can be used is thermal energy. Thermal energy can come from coal, solar energy, geothermal or waste heat from industries that are no longer used. The purpose of this study was to determine the discharge, pump power and maximum efficiency. The working fluid used is diethyl ether. The heat comes from an electric stove which will heat the working fluid, namely diethyl ether. The variables measured were temperature, volume and pumping time. Variables that are varied are variations in the height of the pumping head, (1) 170cm, (2) 244cm and (3) 325cm. Variations in the volume of diethyl ether in the reservoir tube, (1) 653ml, (2) 717ml and (3) 844ml. Variations in the volume of compressed air in the compressed tube, (1) 5.49 liters, (2) 4.71 liters, and (3) 3.14 liters. Variations in the use of compressed air tubes, (1) one compressed air tube and (2) two compressed air tubes. The results showed that the maximum discharge of 0.63 liters/minute was obtained at variations in the height of the pumping head 1.7m, ether volume 653ml, compressed air volume 3.14 liters, and using one compressed air tube. The maximum pump power of 0.185 watt and the maximum pump efficiency of 0.047% were obtained at variations in pumping head height of 3.25m, volume of ether 653ml, compressed air volume of 3.14 liters, and using one compressed air tube.